Risk factors of athletes who used first aid stations and retired during triathlon competitions - Okada, T; Kasanami, R; Kuramoto, R; Ishii, N; Hamai, A (Japanese Journal of Clinical Sports Medicine, 2023)
Many cases of sudden death have been reported during triathlon competitions, and most frequently occur during the swimming part. However, measures to reduce the risk of sudden death are unknown. We conducted a cross-sectional study to explore the risk factors of athletes who used the first aid station and retired during triathlon competitions in 2014. A questionnaire survey on the condition of participants was conducted on the day before the event. Those who used the first aid station and retired from the competition were defined as the “event group.”The Mann-Whitney U test and the χ-square test were used for analysis. Alcohol consumption on the day before the event was also surveyed. The number of participants was 718; nine were classified into the event group, and seven of them retired during the swimming part. Those in the swimming part event group (p＜0.05), had practiced less in an open water swimming situation (OWS) and had shorter experience of OWS (p=0.06).One case, who was transported by ambulance, had drunk sixty grams of alcohol the previous night. A relatively low frequency and experience of OWS could be a risk factor for athletes who used the first aid station and retired during triathlon competition. Alcohol consumption the previous night may also be a risk factor.